Personal Reflections on Muskogee Men and Matriculture: Transcript - Gray, Jeffrey (Matrix)

(untitled) (International Network for Training, Education, and Research on Culture, 2025)
In this recorded interview, Jeff Gray shares his thoughts about being a Muskogee man and what this means, as well as exploring the role of Muskogee men in the lives of Muskogee women. Transcript available (see PDF).LINK TO VIDEO INTERVIEW: Personal Reflections on Muskogee Men and Matriculture, Jeff Gray